2011
DOI: 10.1002/app.36331
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of aluminum oxide–poly(ethylene‐co‐butyl acrylate) nanocomposites

Abstract: This article describes the preparation and characterization of composites containing poly(ethylene-cobutyl acrylate) (EBA-13 and EBA-28 with 13 and 28 wt % butyl acrylate, respectively) and 2-12 wt % (0.5-3 vol %) of aluminum oxide nanoparticles (two types differing in specific surface area and hydroxyl-group concentration; uncoated and coated with, respectively, octyltriethoxysilane and aminopropyltriethoxysilane). A greater surface coverage was obtained with aminopropyltriethoxysilane than with octyltriethox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…The C1-coated nanoparticles had the highest coverage of silane on the nanoparticle surface, 5.5 molecules (nm) À2 . This value was higher than the coverage of aminopropyltriethoxysilane on aluminium oxide nanoparticles reported by Nordell et al [6] and Wåhlander et al [7], which was attributed to the low steric hindrance of the methyl groups (C1) and the formation of multilayers in this silane coating. The silsesquioxane coverage was lower for the silanes with longer alkyl units ( Table 2).…”
Section: Characterisation Of Functional Silane-coated Particlesmentioning
confidence: 77%
See 1 more Smart Citation
“…The C1-coated nanoparticles had the highest coverage of silane on the nanoparticle surface, 5.5 molecules (nm) À2 . This value was higher than the coverage of aminopropyltriethoxysilane on aluminium oxide nanoparticles reported by Nordell et al [6] and Wåhlander et al [7], which was attributed to the low steric hindrance of the methyl groups (C1) and the formation of multilayers in this silane coating. The silsesquioxane coverage was lower for the silanes with longer alkyl units ( Table 2).…”
Section: Characterisation Of Functional Silane-coated Particlesmentioning
confidence: 77%
“…Different methods have been used to prepare polymer nanocomposites, including melt mixing [6], solution mixing [7] and in-situ polymerisation [8]. The incompatibility between nanoparticles and polymer matrix is usually a challenge and it may lead to particle agglomeration and void formation in the composites, which in some cases have detrimental effects on the performance of the materials [9].…”
Section: Introductionmentioning
confidence: 99%
“…The ND particles had a near spherical shape with an average particle diameter of 45 nm and the specific surface area of 36 m 2 /g. SEM analysis of uncoated ND particles as received from manufacturer showed that the average particle diameter is ca 45 nm [9]. The SEM pictures of both types of nanoparticles are shown in Figure1.…”
Section: Methodsmentioning
confidence: 98%
“…Aminopropyltriethoxy silane and octyltriethoxy silane were used for surface modification of the nanoparticles and were supplied by Sigma-Aldrich and Fluka respectively. According to TGA the grafting density was calculated to be: 0.4 -1.4 octylterminated silane molecules and 1.4 -2.5 amino-terminated silane molecules per square nanometer for ND and NA nanoparticles respectively; based on the assumption that a uniform silane layer was formed around each nanoparticle [9]. The stabilizer Irganox 1010 (a hindered phenolic antioxidant) was provided from Ciba Specialty Chemicals, Germany.…”
Section: Methodsmentioning
confidence: 99%
“…The alumina nanoparticles used were almost completely spherical with diameter < 50 nm according to the data from the manufacturer. Examining uncoated particles as received from manufacturer showed that the average particle diameter is ca 45 nm [8], see Figure 1. …”
Section: A Materialsmentioning
confidence: 99%